5(2y+2)-(y+3)=

Simple and best practice solution for 5(2y+2)-(y+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2y+2)-(y+3)= equation:


Simplifying
5(2y + 2) + -1(y + 3) = 0

Reorder the terms:
5(2 + 2y) + -1(y + 3) = 0
(2 * 5 + 2y * 5) + -1(y + 3) = 0
(10 + 10y) + -1(y + 3) = 0

Reorder the terms:
10 + 10y + -1(3 + y) = 0
10 + 10y + (3 * -1 + y * -1) = 0
10 + 10y + (-3 + -1y) = 0

Reorder the terms:
10 + -3 + 10y + -1y = 0

Combine like terms: 10 + -3 = 7
7 + 10y + -1y = 0

Combine like terms: 10y + -1y = 9y
7 + 9y = 0

Solving
7 + 9y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 9y = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 9y = 0 + -7
9y = 0 + -7

Combine like terms: 0 + -7 = -7
9y = -7

Divide each side by '9'.
y = -0.7777777778

Simplifying
y = -0.7777777778

See similar equations:

| abs(3x-4)= | | 1/3t-4/3=5/4t-3/2 | | 3(2x-1)-2(x-4)= | | 8m-5=6m-8 | | (5x-4)(4x+9)=0 | | 4(x+5)+3(x-6)= | | -136-10x=43-17x | | 45x^5+60x^2+15x= | | -2r+3=6-1/2r | | 1150+600+4x=800+400+9x | | x^2-14x-37=-8x+3 | | 1+3(-4z+7)=(z-8)-4 | | 1/2r | | m/n=p/q | | -v-4=3v | | 4(2x+3)-(x-2)= | | 2y/3-y/4=15 | | 2x^2+16x+32=17 | | 90x^2+84x^9+105= | | 7(2x+3)=4(x-5)-17 | | -v+12= | | X^4-18x^2+18=o | | -x^2-2x+1=9 | | x+3+7x-9=82 | | 5(y+-7)+-2y=1+-3[(4y+7)+-2(y+-3)] | | 10r-r= | | 5x^2+26x+32=0 | | 3(4x-2y)+2(x+2y)= | | 2x+11=6x-5-4x | | 11x-3=2x+9 | | 4x/3+2=5 | | -35x+12=28x+19 |

Equations solver categories